As relações socioeconômicas na feira do produtor de Francisco Beltrão - PR - Duarte, André (2018)
Market access has been decisive in guaranteeing the living conditions and reproduction of family farmers, and can not be seen only as risks to these actors. In this way, the debate around the markets as social constructions, taking the actors as protagonists has gained space in the rural studies. Therefore, this dissertation is inserted in the discussion of the markets of the familiar farmers, taking as objective of analysis the trajectory of the Fair of the Producer, located in the central square of the municipality of Francisco Beltrão – PR.Considering this experience as a market socially constructed by the local actors, it is sought to characterize the context of origin of this fair, its historical and organizational aspects, as well as who are the actors protagonists of this experience and that relations were established over time and space . It is a descriptive case study with mixed methodology, so that even with an emphasis on qualitative analysis, quantitative and qualitative data were used, mainly raised through a semi-structured interview directed to the actors considered protagonists in the origin of the Producer's Fair.The results show that the Producer's Fair originated in the midst of the process of modernization of the agricultural area of the region, where farmers will need to create alternatives for their social reproduction. Thus they had their capacity of agency activated before a field in transformation, setting up an arena that made possible the approach with other actors and the construction of an alternative of commercialization. Therefore, it is a socially constructed market experience, which depends on relationships based on principles of reciprocity, solidarity, trust and domesticity as a way of guaranteeing the existence of the actors, which does not mean that this experience is free of relationships too interests.